Effects of novel additives for zinc-nickel alloy plating - Gezerman, Ahmet Ozan (European Journal of Chemistry, 2019)
The development of alternative coating material is important for the corrosion life of metals. Improving the corrosion resistance and decorative appearance of zinc-nickel coatings is gaining importance. Related physical properties can be provided by using various chemicals. Tetraethylamine, triethanolamine, gelatin, and p-aminobenzenesulfonic are the chemicals used in this study to evaluate corrosion resistance and decorative appearance.